Accuracy of digital panoramic regarding interproximal caries detection - Goodarzi Pour D; Nejati S; Fotouhi A (Tehran University of Medical Sciences, 2011)
"nBackground and Aims: Conventional radiological equipments in our country are going to be converted to digital system using computed radiology (CR) technology. If we know the accuracy of digital panoramic radiography for detection of small defects in tooth, it will be useful in cases with difficulty for taking the intraoral radiographs. The aim of this study was to evaluate sensitivity and specificity of digital panoramic radiography for detection of proximal caries compared with the bitewing radiography."nMaterials and Methods: One-hundred patients who had been ordered for taking both bitewing and panoramic radiography were included in this study. Panoramic and then bitewing radiographs were observed by a maxillofacial radiologist and interproximal caries were recorded. Sensitivity and specificity of digital panoramic radiography (CI=95%) was calculated compared with the bitewing radiography as a gold standard."nResults: This study showed that the values for sensitivity and specificity were 62.7% (CI 95%=57.7%-67.5%) and 91.0% (CI 95%=89.2%-92.5%), respectively."nConclusion: Sensitivity of digital panoramic is less than bitewing radiography even with processing before printing. Therefore, bitewing radiography is superior for detection of inter proximal caries.